Software product lines structuring based upon market demands. - Ereño, Montse (Software engineering notes.)
Nowadays the increasing demand for customized products and services in traditional areas such as Automotion Manufacturing or Aeronautical Component Engineering is being satisfied with a new approach called "Product Platform". This successful approach is also being considered in the design of software-based components in these areas, which are recognized as complex and critical.In this paper, we present the research that is being carried out at Mondragon University. This effort focuses on the analysis of existing Product Platform Development methods and the transference of this know-how to Software Product Development.As a result, a Software Product Line (SPL) development method will be defined and applied in a real case. This method will be based upon market demands, so it should be flexible enough to respond to customer's requests and market pressure. In this paper we will explain in detail one step of the process. This step is concerned with how QFD technique can be used to the specification of components in a SPL.